Epidemiological Situation on Tick-Borne Viral Encephalitis in the Russian Federation in 2011–2021 and Short-Term Forecast of its Development - A. Ya. Nikitin; E. I. Andaev; M. I. Tolmacheva; N. I. Ayugin; E. V. Yatsmenko; V. A. Matveeva; A. O. Turanov; S. V. Balakhonov (Проблемы особо опасных инфекций, 2022)
The aim of the work was to analyze the epidemiological situation on tick-borne viral encephalitis in the endemic territories of the Russian Federation in 2021 in comparison with the dynamics over 2011–2020 and its shortterm forecast for 2022. In Russia, 48 constituent entities belonging to seven federal districts are endemic for tick-borne viral encephalitis (TBVE). There is a statistically significant downward trend in the incidence of TBVE in the Siberian Federal District (which is characterized by the maximum incidence rate in the country), the Volga and Far Eastern Federal Districts. In the Ural Federal District (the second in terms of TBVE incidence), the decline in the incidence has stalled since 2021. The average long-term incidence of TBVE in the constituent entities of the Russian Federation varies from sporadic (Republic of Crimea)  up to 12.5 per 100 thousand of the population (0/0000) (Krasnoyarsk Territory). In 2021, TBVE cases were detected in 42 endemic regions and in one non-endemic region – Stavropol Territory. At the same time, 1015 cases of TBVE were in the country (0.69 0/0000). In all Federal Districts, the incidence of TBVE is below the long-term average values. Using the Quantum GIS program, the incidence of TBVE in 917 administrative territories of the country has been ranked and grouped according to the level of epidemiological risk. This made it possible to establish that 65 % of the territories form a zone of low epidemiological risk. High and very high epidemiological risk is observed in 13% of the analyzed districts. The structure of TBVE clinical manifestations in 2021 was dominated by febrile (59.7 %) and meningeal (24.3 %) forms. 14 lethal outcomes were reported. In 2021, 2 889 515 people were vaccinated (including 1 433 850 children), of which 14 fell ill. Specific immunoglobulin was used to prevent the overt development of infection in 100 704 individuals, which accounts for 22.6 % of the persons affected by tick bites (30.6 % among children). Acaricidic treatments were carried out on an operational area of 233 125 hectares of territories of socially significant objects. The scope of all TBVE prevention measures in 2021 increased as compared to 2020. In 2022, a decline in the incidence of TBVE in endemic Federal Districts and in the country on the whole is forecasted to (0,64±0,192) 0/0000.